1998
DOI: 10.1021/ef980074k
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Correlation of 13C NMR Chemical Structural Analyses of Coal Based on Elemental Composition and Volatile Matter Content

Abstract: 13C NMR spectroscopy has been shown to be an important tool in the characterization of coal structure. Important quantitative information about the carbon skeletal structure is obtained through 13C NMR spectral analysis of coal. Solid-state 13C NMR analysis techniques have progressed beyond the mere determination of aromaticity and can now describe features such as the number of aromatic carbons per cluster and the number of attachments per aromatic cluster. These 13C NMR data have been used to better understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(148 citation statements)
references
References 15 publications
2
145
0
1
Order By: Relevance
“…The CPD model is based on the chemical structure of coal and treats coal as a lattice of aromatic rings and models coal thermal decomposition approximating the breakdown of the macromolecular network. In this paper, the chemical structure parameters are obtained by nonlinear correlations (Genetti et al, 1999) between data from chemical analysis of coal and those from 13 C NMR analysis. The proximate and ultimate analysis of the coal used in the 2 MW pilot plant is shown in Table 3.…”
Section: Coal Reaction Sub-modelsmentioning
confidence: 99%
“…The CPD model is based on the chemical structure of coal and treats coal as a lattice of aromatic rings and models coal thermal decomposition approximating the breakdown of the macromolecular network. In this paper, the chemical structure parameters are obtained by nonlinear correlations (Genetti et al, 1999) between data from chemical analysis of coal and those from 13 C NMR analysis. The proximate and ultimate analysis of the coal used in the 2 MW pilot plant is shown in Table 3.…”
Section: Coal Reaction Sub-modelsmentioning
confidence: 99%
“…Furthermore, with a variation between 0 and 6% its range of tolerance is even smaller than the error of the 13 C CP-MAS NMR being between 2 and 15 mole carbon % as estimated by Snape et al (1989). Genetti et al (1999) applied the carbon content as described in equation (5). But in comparison to the measured aromaticity values it becomes apparent, that this method results in considerably too low values for both raw coal and pyrolysis residues.…”
Section: Adaptability Of Published Modelsmentioning
confidence: 99%
“…So, later on further research by Retcofsky and Link (1978) revealed that this method results in too high carbon aromaticity values. Apart from van Krevelen (1953), further work was done for calculating the carbon aromaticity by Jones et al (1986), Carr and Williamson (1989), Rentrop (1989), Maroto-Valer et al (1994), Mazumdar (1999) and Genetti et al (1999). All of their models have the advantage that they were verified by NMR-spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Through the C NMR spectroscopy is possible to obtain the chemical structure of the coal [16]. The CPD model requires five input parameters, which can be determined from the C NMR spectroscopy, which is a very complex procedure.…”
Section: Matematical Modelmentioning
confidence: 99%
“…Schaffel et al [9] utilized the IFRF experimental data in order to characterize both devolatilization and charcombustion processes, and thus determine the five parameters of the CPD model. Since this procedure are expensive and time consuming, in this work has been used the Genetti correlations [16], which correspond to a series of non-linear correlations able to estimate the five parameters. These parameters are: Mdel, Mcl, σ+1, p0 and c0.…”
Section: Matematical Modelmentioning
confidence: 99%